PENENTUAN KEBIJAKAN INVENTORI SPARE PART PT X UNTUK MEMINIMASI TOTAL BIAYA INVENTORI DENGAN MEMPETIMBANGKAN SERVICE LEVEL - Anugrah Putra, Dhany
Indonesia heavily relies on non-renewable natural resources, particularly oil and gas, which still account for 84.5% of the country's total energy. The PwC report (2023) indicates that oil and gas companies in Indonesia have substantial investments and significant spare parts inventory values, with poor management potentially leading to significant losses due to downtime. This study focuses on PT X, which uses Oracle software for inventory management, but still faces challenges in achieving a service level target of 99.9% due to irregular demand patterns and stock-out issues. The study emphasizes the importance of accurate strategies in determining the quantity of spare parts to optimize operational efficiency and minimize costs. The research aims to determine the minimum and maximum values of the min-max inventory model using the Revised Power Approximation (RPA) approach. The RPA approach can yield near-optimal results with simpler computation (Ehrhardt & Mosier, 1984). After determining the minimum and maximum values, simulations were conducted to calculate the total inventory costs and service level for the next 10 years, comparing the existing inventory policy with the proposed policy to assess their performance. Based on the research findings, the proposed inventory policy provides significant improvement. Over the next 10 years, the proposed policy results in an 18.53% lower total inventory cost, amounting to $197,837.51, and improves the service level to 99.7%, which is 9.14% better than the existing policy. Thus, it can be concluded that the proposed inventory policy outperforms the existing policy in terms of cost efficiency and service level.